Adsorption-energy-based activity descriptors for electrocatalysts in energy storage applications. Issue 3 (25th September 2017) - Wang, Youwei; Qiu, Wujie; Song, Erhong; Gu, Feng; Zheng, Zhihui; Zhao, Xiaolin; Zhao, Yingqin; Liu, Jianjun; Zhang, Wenqing
Abstract: Energy storage technologies, such as fuel cells, ammonia production and lithium–air batteries, are important strategies for addressing the global challenge of energy crisis and environmental pollution. Taking overpotential as a direct criterion, we illustrate in theory and experiment that the adsorption energies of charged species such as Li + + e − and H + + e − are a central parameter to describe catalytic activities related to electricity-in/electricity-out efficiencies. The essence of catalytic activity is revealed to relate with electronic coupling between catalysts and charged species. Based on adsorption energy, some activity descriptors such as d -band center, eg -electron number and charge-transfer capacity are further defined by electronic properties of catalysts that directly affect interaction between catalysts and charged species. The present review is helpful for understanding the catalytic mechanisms of these electrocatalytic reactions and developing accurate catalytic descriptors, which can be employed to screen high-activity catalysts in future high-throughput calculations and experiments.